Exploring Ecosystem Concepts - A Topic Modeling Approach - Kirschbaum, Julius; Winkler, Christian (EURAM 2024, 2024)
In contrast to previous literature reviews, this paper takes a computational approach to discriminate the numerous ecosystem concepts within the broader business and management literature. It aims to enable researchers to specify the types of ecosystems in the focus of their studies. While most previous research was based on comparatively small sample sizes, the computational approach employed in this research enables the analysis of a large dataset on ecosystem literature. Three topic modeling techniques and inductive category formation are utilized to identify ecosystem themes and concepts within various strands of research based on abstracts of academic literature. Results indicate the use of three perspectives on ecosystems: ecosystem as a catchphrase, ecosystem as a phenomenon, and ecosystem as a concept. Moreover, nine ecosystem themes with different uses of the term ‘ecosystem’ are identified. Based on the reviewed literature associated with each theme, seven preliminary dimensions are derived that define the characteristics of an ecosystem: the underlying view of the nature of an ecosystem as a metaphor vs. as an analogy and as a phenomenon vs. as a concept, context or domain, central element/nucleus, locality, ecosystem goal/outcome, types of entities and links between them. These dimensions enable research to specify the phenomena and concepts that they and thereby support rigorous study design.<br
Keywords: ecosystem concepts; ecosystem characteristics; literature analysis